EFEKTIVITAS TEKNIK MEMBACA ACCELERATED LEARNING TERHADAP KEMAMPUAN MENULIS RESENSI BUKU PADA SISWA KELAS XI SMA NEGERI 1 KISAM ILIR PALEMBANG - Indah Rohmalinda (STIT Al-Ittihadiyah Labuhanbatu Utara, 2022)
Abstract: This study aims to determine the effectiveness of the Accelerated Learning Reading Technique on the ability to write book reviews in class XI students of SMAN 1 Kisam Ilir in 2020/2021. The population of this research is class XI students consisting of 3 classes totaling 95 students. The sample of this study was two classes totaling 62 students. Class XI MIA 1 as the experimental class and class XI IIS 2 as the control class. This research method is an experimental method with a quantitative approach. In this study, an essay test was used after the end of learning (post test) to determine the students' ability to write book reviews with the implementation of Accelerated Learning technique or not. The results of data analysis on the control class without using the Accelerated Learning technique on 31 students obtained an average value of 74.19. Meanwhile, in the experimental class, the results of the data with the implementation of the Acceleraed Learning technique on 31 students obtained an average score of 77.64. This means that students' ability to write book reviews is at a very good level due to the effectiveness of Accelerated Learning's learning techniques. Based on the results of the calculation of the hypothesis test data obtained t_(count ) of 6.27. Furthermore, t_count is compared with t_(table) with a significance level of 0.05 with dk=60. It is obtained that the price of t_table = 2,000 means that t_hitung≥ t_table is 6.27 2,000. Thus, there is an effective use of Accelerated Learning learning techniques on the ability to write book reviews in class XI students of SMAN 1 Kisam Ilir.